Soil Electrical Conductivity as One Possible Tool for Predicting of Cirsium Arvense Infestation Occurrence - Kroulik, Milan; Slejska, Atonin; Kokoskova, Dana; Venclova, Veronika (IntechOpen, 2011)
None